New taxonomic assignments of Calisiinae with description of two new genera (Hemiptera, Heteroptera, Aradidae) - Heiss, Ernst (Zootaxa, 2015)
Examination of type species of Calisius pallipes Stål 1860 from Brazil and Calisius ghiliani (A.Costa 1864) from Europe has revealed essential morphological differences warranting their placement into different genera. Stål’s pallipes is the genotype of Calisius, and ghiliani that of Aradosyrtis A.Costa, whose generic status is revived. A neotype is designated for Aradosyrtis ghiliani A.Costa 1864. Clearly distinguished from Calisius sensu Stål are the Neotropical Calsius farri Kormilev 1964 and the African Calisius lativentris Horvath 1913, for which the new genera Caribocalisius n.gen and Afrocalsius n.gen are established, respectively.